Pendampingan Pemberdayaan Posyandu Balita Desa Pilangsari Gondang Kabupaten Klaten - Marjukah, Anis; Nugroho, Arif Julianto Sri; Winarno Heru Murjito; Hartanto; DBP Setiyadi; Sigit Adhi Pratomo; Sri Haryanti; Purwo Haryono; Hersulastuti (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
The assistance activity for empowering Posyandu (integrated service center) toddlers in Pilangsari Gondang Village, Klaten Regency aims to improve the quality system of Posyandu services, increase the participation of mothers and young women in serving the community so that the effectiveness of activities to fight toddler stunting in the village is achieved. The model of activities carried out includes: 1) Service-Quality Capacity Building for Posyandu services for toddlers, 2) Technology Transfer. To achieve this goal, several activities are carried out in assistance: a) Evaluation of the quality of Posyandu for toddlers b) Establishment of a Service-Quality network (c) Training and development of healthy toddler services to fight stunting d) Improvement of supporting facilities/infrastructure to develop services f) entrepreneurial training for making dry and wet cakes based on village characteristics to improve nutrition for toddlers and the community. Based on activities, the results of an effective activity model are obtained, where mothers and young women are enthusiastic about participating in the program and this lead to the formation of a foundation for empowering the quality of excellent toddler Posyandu services in the village to fight toddler stunting.